Kontribusi Motivasi, Kemandirian Belajar dan Lingkungan Belajar terhadap Hasil Belajar Matematika Siswa Kelas X SMK Muhammadiyah Delangggu Klaten Tahun Ajaran 2014/2015 - Wati, Lutfi Mei Kuncoro; , Drs.Ariyanto,.M.Pd (2015)
Mathematics learning outcomes are the changes that happen to the students after doing the math learning process. Such changes as the student learning experience which includes cognitive, affective, psychomotor. Mathematics learning outcomes in SMK Muhammadiyah Delanggu including low. This can be seen from the average national math test scores in 2013/2014, which only reached 5.86. Research purposes, (1) examine the contribution of motivation on the results of students' mathematics learning, (2) learning independence to examine the contribution of mathematics learning outcomes, (3) examine the contribution of the learning environment for mathematics learning outcomes, (4) test jointly contribute motivation, independent learning, learning environment for mathematics learning outcomes. This research is quantitative with descriptive correlational design. The research sample 59 students of class X SMK Muhammadiyah Delanggu. Techniques of collecting data using questionnaires and documentation. Data were analyzed using multiple regression analysis. The results of the study, (1) There is a positive and significant contribution motivation to mathematics learning outcomes by contributing 12.19%, (2) There is a positive and significant contribution to the learning outcomes independent learning mathematics with the contribution of 10.46%, (3) There is a positive contribution and significant learning environment for mathematics learning outcomes with the contribution of 12.25%, (3) There is a positive and significant contribution motivation, independent learning, and the learning environment for mathematics learning outcomes with the contribution of 34.9%.